A formação continuada de professores do ensino fundamental no município de Vargem Grande: reflexos na prática docente - MONTEIRO, Roseanne Márcia Silva Marques (2020)
This Master's Dissertation is part of the research group “School, Curriculum and Teacher Training” at the Federal University of Maranhão - UFMA and deals with the continuing education of elementary school teachers in the municipality of Vargem Grande / MA, whose main objective is to analyze the continuing education of teachers in the 1st stage of elementary education (1st to 5th year) of the Municipal Education Network of Vargem Grande / MA and its effects on teaching practice. To carry out the research, the qualitative approach was used, with the use of instruments and techniques of bibliographic and documentary research, focus group and interviews. The research was carried out in two municipal elementary schools in the first stage and included 14 (fourteen) subjects, being: 10 (ten) teachers, 2 (two) managers and 2 (two) pedagogical advisors. The questions addressed aspects about concepts of continuing education, identification of the relationship between theory and practice in pedagogical action based on continuing education, contributions from continuing education as a proponent of new paths and discoveries for the teacher's pedagogical practice. The study considered the training carried out by the SEMED / VG Training Coordination in the period from 2017 to 2019. The theoretical and methodological references that support this discussion about this object are supported by authors such as: Freitas (2002); Duarte (2003); Martins (2010); Gatti (2005); Tardif (2000); Tanuri (2000); Azavedo (2003); Libâneo (2009); Gamboa (2012), Poupart (2010); Minayo (2010); among others. The research adopts the historical-critical theory outlined by Demerval Saviani (1993, 1997, 2003, 2007, 2011a, 2011b) as an epistemological assumption. It was concluded with the study that the discussions about the continued formation of teachers in the school spaces are fundamental to realize if the way it is being conducted, is reproducing the hegemonic interests or if it is seeking to favor more democratic educational practices, in order to provide teachers with the perception of the need to practice teaching critically in order not to serve as an instrument of reproduction. It is in this direction that we advocate continuing teacher education that is beyond the immediacy of practice, but that broadens critical thinking, produced in a collective and contextualized way, that considers practical and theoretical knowledge, relating them dialectically, with a view to the construction training that takes new paths.